Invited Lecture 4: New diagnostic assays for COVID-19 - Sumanta Goswami (Wolters Kluwer Medknow Publications, 2020)
Brief Biosketch Dr Sumanta Goswami did his MS from University of Calcutta and PhD in Biochemistry from AIIMS, New Delhi. He joined at Albert Einstein College of Medicine, New York as Research Associate and subsequently becomes Associate Professor in the Department of Anatomy and Structural Biology. His research identifies newer drug targets based on the phenotypes observed in the cancer cells that cause metastasis. In the recent COVID-19 pandemic the diagnostic world has made phenomenal progress by developing different molecular diagnostic and serological assays for SARS-CoV-2 within record time. In my talk, I will outline the different molecular diagnostic and serological tests that are available and in use today. In addition, I will focus on a few new tests that are on the horizon including a subgenomic mRNA detection test being developed by our group. This unique test is arguably capable of identifying patients with active infections and thereby focusing the isolation resources on patients who are actively shedding live virions.